Optimization of Mechanical Properties in Sago Cellulose-based Biodegradable Films for Sustainable Packaging - Josephine Chang Hui, Lai; Jessica Jane, Donald; Mohd Farid, Atan; Sherena, Sar‑ee (The Italian Association of Chemical Engineering, 2025)
Environmental concerns over plastic waste have accelerated research into biodegradable packaging. This study optimizes the mechanical properties of sago cellulose-based films using Response Surface Methodology (RSM) with a Central Composite Design (CCD). The key formulation factors investigated include glycerol content, pre-treated sago waste (PSW) content, and alkali treatment concentration, which significantly influence the film’s elongation at break (EAB), tensile strength (TS), and Young’s modulus (YM). The model developed demonstrated a strong correlation with an R² value of more than 0.5, confirming the model's adequacy. The optimized biofilm formulation achieved 12.547 MPa in TS, 100.421 % in EAB, and 97.499 MPa in YM, indicating a balance between strength and flexibility. The findings suggest that sago cellulose-based films have strong potential as sustainable packaging materials, offering an eco-friendly alternative to synthetic plastics.